What Is Global History? - Conrad, Sebastian (Book collections on Project MUSE., 2016)
"Until very recently, historians have looked at the past with the tools of the nineteenth century. But globalization has fundamentally altered our ways of knowing, and it is no longer possible to study nations in isolation or to understand world history as emanating from the West. This book reveals why the discipline of global history has emerged as the most dynamic and innovative field in history--one that takes the connectedness of the world as its point of departure, and that poses a fundamental challenge to the premises and methods of history as we know it. What Is Global History? provides a comprehensive overview of this exciting new approach to history. The book addresses some of the biggest questions the discipline will face in the twenty-first century: How does global history differ from other interpretations of world history? How do we write a global history that is not Eurocentric yet does not fall into the trap of creating new centrisms? How can historians compare different societies and establish compatibility across space? What are the politics of global history? This in-depth and accessible book also explores the limits of the new paradigm and even its dangers, the question of whom global history should be written for, and much more. Written by a leading expert in the field, What Is Global History? shows how, by understanding the world's past as an integrated whole, historians can remap the terrain of their discipline for our globalized present"--Provided by publisher.